Reading strategies for mathematics - Brummer, Trisha. 4 0 16; Macceca, Stephanie; 5 (Huntington Beach, CA : Shell Education, 2008)
Offers practical, standards-based strategies designed to help teachers of grades one through eight create mathematics lessons and activities that will improve students' ability to read, write, and understand mathematics. Includes a CD-ROM with reproducible graphic organizers and activity sheets.
Includes bibliographical references (p. 204-208).
Professional;Professional
System requirements not stated.
Keywords: 2 -- 0; 6; Study and teaching.;Aids and devices.;Study and teaching.;Aids and devices. -- Mathematics;Teaching;Creative activities and seat work.;Mathematics;Teaching;Creative activities.;CD-ROMs.; 20; CD-ROMs.